Influence of prior knowledge and repetition of interviews: memory and suggestion in a sample of preschool students (2019)
Introduction: In recent years criminal cases have increased in which the only available evidence is in the form of a statement from a minor. This has motivated the search for factors that may affect the accuracy and credibility of a statement. The present study focuses on the influence of prior knowledge and the repetition of interviews with regards to memory and the acceptance of suggestion in a sample of preschool students. Methodology: Twenty-six preschool students participated in three sessions. In the first session, half of the participants were shown a bag hanger (a previously unknown object), and the other half were taught how to use it and were permitted to manipulate it. In sessions 2 and 3, two interviews were conducted and in each of them closed questions were asked about real and false actions, supposedly carried out in session 1. Results: The results showed that the experienced group generally provided more details about the actions experienced with the bag hanger when compared to the inexperienced group. However, this difference was eliminated in session 3, due to the repeated interview. As for the false actions, a limiting effect was found in the acceptance of the suggestion, and both groups gave a similar amount of detail in sessions 2 and 3. Conclusions: Prior knowledge influences the amount of detail provided only if asked once. If the questions are repeated, the effect disappears.